(untitled) (TAMADDUN NURI JURNALI, 2024)
This article reveals the essence of the views of S.Freud, the founder of psychoanalysis, the ability to correctly apply psychological methods in the client-psychologist-psychotherapist relationship, as well as the knowledge underlying any problem, pathology, disease in the process. Psychological consultation creates a theoretical basis for identifying and eliminating this or that psychological trauma.